Sodium‑glucose cotransporter 2 inhibitors (SGLT2i): renal implications (2020)
Type 2 diabetes mellitus (DM2) is a chronic condition that affects more than 400 million individuals worldwide. In DM2 patients, an appropriate glycemic control slows the onset and delays the progression of all its micro and macrovascular complications. Even though there are several glucose-lowering drugs, only approximately half of patients achieve glycemic control, while undesirable adverse effects (e.g., low serum glucose) normally affect treatment. Therefore, there is a need for new types of treatments. Sodium-glucose cotransporter 2 inhibitors (SGLT2i) have just been developed for treating DM2. Renal hyperfiltration as a marker of increased intraglomerular pressure in diabetic patients, and the role of renin–angiotensin– aldosterone system (RAAS) in this phenomenon have been studied. Nevertheless, RAAS blockade does not completely reduce hyperfiltration or diabetic renal damage. In this sense, the contribution of renal tubular factors to the hyperfiltration state, including sodium–glucose cotransporter (SGLT), has been currently studied. SGLT2i reduce proximal tubular sodium reabsorption, therefore increasing distal sodium delivery to the macula densa, causing tubule-glomerular feedback activation, afferent vasoconstriction, and reduced hyperfiltration in animal models. In humans, SGLT2i was recently shown to reduce hyperfiltration in normotensive, normoalbuminuric patients suffering from type 1 diabetes mellitus. In DM2 clinical trials, SGLT2 is associated with significant hyperfiltration and albuminuria reduction. The aim of this article is to compile the information regarding SGLT2i drugs, emphasizing its mechanism of renal repercussion.